A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam - Nguyen, Truong Quang; Pham, Anh Van; Ziegler, Thomas; Ngo, Hanh Thi; Le, Minh Duc (Zootaxa, 2017)
We describe a new species of Cyrtodactylus on the basis of four specimens collected from the limestone karst forest of Phu Yen District, Son La Province, Vietnam. Cyrtodactylus sonlaensis sp. nov. is distinguished from the remaining Indochinese bent-toed geckos by a combination of the following characters: maximum SVL of 83.2 mm; dorsal tubercles in 13–15 irregular rows; ventral scales in 34–42 rows; ventrolateral folds prominent without interspersed tubercles; enlarged femoral scales 15–17 on each thigh; femoral pores 14–15 on each thigh in males, absent in females; precloacal pores 8, in a continuous row in males, absent in females; postcloacal tubercles 2 or 3; lamellae under toe IV 18–21; dorsal head with dark brown markings, in oval and arched shapes; nuchal loop discontinuous; dorsum with five brown bands between limb insertions, third and fourth bands discontinuous; subcaudal scales distinctly enlarged. In phylogenetic analyses, the new species is nested in a clade consisting of C. huongsonensis and C. soni from northern Vietnam and C. cf. pulchellus from Malaysia based on maximum likelihood and Bayesian analyses. In addition, we record Cyrtodactylus otai Nguyen, Le, Pham, Ngo, Hoang, Pham & Ziegler for the first time from Son La Province based on specimens collected from Van Ho District.